The Impactful academic : building a research career that makes a difference - Kelly, Wade (Surviving and thriving in academia, 2022)
Globally, researchers are being asked to plan for and demonstrate the impact that their research has on culture, society, health, and the economy. Higher education is changing, moving away from rewarding academics primarily for peer-reviewed academic publications and asking academics to report on how their work contributes to society more broadly. For many academics, impact poses a worrisome proposition. Impact has not generally been integrated into PhD training and many universities have been slow to respond to the emerging impact agenda, leaving a knowledge, training, and support gap. The Impactful Academic offers a holistic, all-of-career approach to impact aimed at active researchers and those who support research impact. It ruminates on the question of what an academic with impact looked like in the past, and what it will look like going forward as concepts around impact are solidified by government and granting agencies. The authors come from various backgrounds including engaged scholars who are generating impact, and impact professionals who have been critical to supporting academics across disciplines on their impact journeys. The reader will emerge with more than an impact plan for a single research project or grant, but rather a holistic, career-centric approach to impact.